2016
DOI: 10.1039/c6nr06041b
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes stimulate synovial inflammation by inducing systemic pro-inflammatory cytokines

Abstract: a Carbon nanotubes (CNTs) have promising applications in a wide range of biomedical fields, including imaging, drug/gene delivery and other therapeutics; however, the biosafety concerns of CNTs should be addressed. To date, many reports have documented the toxicological effects on the cells, tissue or organs that are in direct contact with the tubes; however, there is limited evidence to unravel the secondary toxicity upon CNT treatment. Moreover, more effort is needed to gain a definitive understanding of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 100 publications
1
33
0
Order By: Relevance
“…Nonetheless, our combined data depicted the secondary toxicity of MWCNTs in disturbing systemic iron homeostasis through inflammatory pathway, and, nonetheless, PEG and COOH modifications could ameliorate such secondary toxicity. In parallel to the current study, we recently reported a novel secondary toxicity of carbon nanotubes: synovial inflammation due to carbon nanotube‐induced systemic inflammation . Considering the secondary toxicity, especially under long‐term exposure, more investigations are needed to evaluate the biosafety of MWCNTs, regardless of surface modifications.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Nonetheless, our combined data depicted the secondary toxicity of MWCNTs in disturbing systemic iron homeostasis through inflammatory pathway, and, nonetheless, PEG and COOH modifications could ameliorate such secondary toxicity. In parallel to the current study, we recently reported a novel secondary toxicity of carbon nanotubes: synovial inflammation due to carbon nanotube‐induced systemic inflammation . Considering the secondary toxicity, especially under long‐term exposure, more investigations are needed to evaluate the biosafety of MWCNTs, regardless of surface modifications.…”
Section: Discussionmentioning
confidence: 54%
“…We recently discovered another secondary adverse effect of carboxylated multiwall CNTs (MWCNTs‐COOH): MWCNTs‐COOH‐induced pro‐inflammatory cytokines could result in synovial inflammation by undermining the priming state of synoviocytes and chondrocytes . To our knowledge, there has been no study of the potential effects on iron metabolism and RBC formation upon exposure to CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies on fate, transport and effects of ENMs were often conducted with ENM concentrations or doses orders of magnitude higher than what has been reported under the typical environmental conditions, thus it is not clear the relevance of these studies in terms of the implications to the environment and human health. [39][40][41][42][43] However, it is worth noting that despite the high doses used in vitro and in vivo studies, valuable information has been obtained on the mechanism of toxicity and potential adverse effects for ENMs, and measures have been taken to cover a wider dose range for in vitro and in vivo studies and use more sensitive methods such as toxicogenomics to study ENM effects at lower doses. [18,20] To better predict the realistic concentrations of ENMs, models and approaches have been developed based on the estimation of global and regional production, application, and life-cycle of ENMs.…”
Section: Determining Realistic Exposure Scenarios and Dosagementioning
confidence: 99%
“…Future work should also take into consideration the secondary effects in tissues and organs distant from the primary target sites. [40,76,77] vi) In addition, more association and epidemiological studies are needed, especially in an occupational exposure setting to build the link of ENM exposure to health impacts for workers. This requires more accurate dose and exposure measurements for ENMs in the working environment, coverage of more physiological or disease markers, determination of the causal relationships, as well as increase in sample sizes.…”
Section: Health Impacts Under Realistic Exposure Conditionsmentioning
confidence: 99%
“…Nonetheless, it is necessary to note that all the current biomedical applications are based on the predesigned physicochemical properties of nanomaterials without considering their potential transformation in biological settings, which may alter their physicochemical properties and consequently hinder their biomedical applications. For instance, biotransformations may influence how nanomaterials interact with the immune cells (e.g., macrophages) responsible for clearing the "worn-out" particles out of the body 9,10 . Thus, understanding the potential transformations and their effects on the ultimate fate of nanomaterials is critical for ensuring the biosafety of nanomaterials.…”
Section: Introductionmentioning
confidence: 99%